Analysis of wind energy potential; A case study of Kocaeli University campus. (1st October 2019) - Caglayan, Ipek; Tikiz, Ismet; Turkmen, Anil Can; Celik, Cenk; Soyhan, Galina (Gulsen)
Abstract: Determination of the wind energy potential is achieved by point measurement at the place. MERRA software which is generated by NASA provides the point data values. The point data with using Windographer software gives theoretically potential energy of wind turbines in a short time. In this study, the Kocaeli University campus selected a point, where the wind turbines are planned to be implemented. The obtained output power from wind energy will be examined. MERRA software and Windographer software are being used during this energy's production study. The wind speed and direction analysis within 1 h of resolution is being performed at some points by using MERRA program. Windographer automatically defines wind resource data such as wind speed, standard deviation, vertical wind speed, direction, temperature, pressure, and relative humidity. Within the 4 point coordinates properly identified by the software, point "B" was selected. The annual wind data of the point "B" was analyzed and the annual amount of energy was calculated. In this study, GE 1.7-100 wind turbine was used. The generated energy and turbine output power were calculated by the Windographer program.